Precision surgery for colorectal liver metastases: Opportunities and challenges of omics-based decision making. Issue 5 (May 2017) - Jones, R.P.; Brudvik, K.W.; Franklin, J.M.; Poston, G.J.
Abstract: Precision surgery involves improving patient selection to ensure that surgical intervention that is proven to benefit on a population level is the optimal treatment for each individual patient. For patients with colorectal liver metastases (CRLM), existing prognostic scoring systems rely on well-recognised histopathological features such as size and number of lesions. Advances in preoperative imaging algorithms mean that increasingly low volume disease can be detected, improving assessment of these factors. In addition, novel imaging modalities mean that underlying tumour biology and metabolic behaviour during therapy can be assessed. Molecular analysis of tumours can provide crucial prognostic information, with the critical role of RAS/RAF mutations in prognosis well recognised. The optimal source of tissue for this level of analysis is debated, with good concordance between primary and metastatic lesions for some recognised prognostic factors but marked discrepancies for a variety of other relevant mutations. As well as mutational heterogeneity between primary and metastatic lesions, heterogeneity within tumours and dynamic changes in tumour biology over time present a significant challenge in assessing tumour for prognostic biomarkers. Circulating tumour cells offer one potential method of longitudinal tumour analysis, but are limited by current technologies. This review article summarises some of the key advances in prognostication for patients with resectable colorectal liver metastases, as well as highlighting the potential limitations of such an approach.